Elemental 2D Materials: Progress and Perspectives Toward Unconventional Structures. Issue 3 (21st December 2020) - Si, Jingjing; Yu, Jinqiu; Shen, Yu; Zeng, Mengqi; Fu, Lei
Abstract : Elemental 2D materials have attracted a great deal of interest due to their excellent properties for various applications in catalysis, sensing, photonics, intracellular gene regulation, magnetism, superconductivity, and so on. It is broadly accepted that the physicochemical properties are highly associated with their atomic arrangements and coordination. Recent studies have demonstrated that unconventional structures of elemental 2D materials exhibit unexpected physicochemical properties and innovative applications beyond conventional structures. Those unconventional structures bring new life to elemental 2D materials and deserve special attention. However, there are considerable challenges to controllably prepare them due to their metastable characters. Herein, their synthetic strategies are focused on to shed light on the reasonable design of new structures with special atomic arrangements to open up tremendous opportunities for expanding their functionalities and potential applications. In addition, the correlations among the types of unconventional structures, the element types, and corresponding synthetic strategies are uncovered. Finally, based on the achievements in the representative studies, some prospects and potential opportunities for extending the scope of elemental 2D materials with unconventional structures and potentially distinctive applications are provided. Abstract : Recent studies have demonstrated that unconventional structures of elemental 2D material exhibit unexpected physicochemical properties and innovative applications beyond conventional structures, which deserve special attention. This perspective is devoted to focusing on their synthetic strategies for the unconventional structure to shed light on the reasonable design new structures with special atomic arrangements to expand their functionalities and potential applications.